2019
DOI: 10.1038/s41467-019-09815-5
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the dislocation core structure at a van der Waals gap in bismuth telluride

Abstract: Tetradymite-structured chalcogenides such as bismuth telluride (Bi 2 Te 3 ) are of significant interest for thermoelectric energy conversion and as topological insulators. Dislocations play a critical role during synthesis and processing of such materials and can strongly affect their functional properties. The dislocations between quintuple layers present special interest since their core structure is controlled by the van der Waals interactions between the layers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Furthermore, the presence of higher-order layers, with 11-, 13-and 17-atoms, can be seen in parts of lamellae with margins displaying replacement by galena ( Figure 13b-d; see also [1]). The role played by the van der Waals gaps in attracting dislocations [28] is illustrated here by the insertion of an extra atom layer at the boundary between two five-atom layers, leading to formation of a single 11-atom layer (Figure 13b). The sequence is thus converted from regular five-atom stacks into (55.11) stacks.…”
Section: The Identity Of Pbbi 4 Te 4 S 3 and Polytypism Among Pb-bi Cmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the presence of higher-order layers, with 11-, 13-and 17-atoms, can be seen in parts of lamellae with margins displaying replacement by galena ( Figure 13b-d; see also [1]). The role played by the van der Waals gaps in attracting dislocations [28] is illustrated here by the insertion of an extra atom layer at the boundary between two five-atom layers, leading to formation of a single 11-atom layer (Figure 13b). The sequence is thus converted from regular five-atom stacks into (55.11) stacks.…”
Section: The Identity Of Pbbi 4 Te 4 S 3 and Polytypism Among Pb-bi Cmentioning
confidence: 97%
“…Irrespectively of specific chemistry, in all layered chalcogenides, the building modules (anion-anion bonds) are separated from one another by van der Waals gaps [1,2,8,9] and thus cannot be reconciled with the sensu stricto definition of Bi-Pb-sulphosalts [25]. The five-atom atomic arrangement separated by gaps was confirmed by HAADF STEM imaging of natural tellurobismuthite [26] and its synthetic analogue [27][28][29][30]. High-resolution HAADF STEM images of such compounds has allowed further insight into the role played by atomic interfaces, (0001) basal twin boundaries, dislocations and Bi 3 Te 4 defects in Bi 2 Te 3 in controlling thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have been carried out to clarify the influence of twinning on properties of topological insulators including stacking sequences, thickness and composition of layers in model structures, interface coherence, surface termination and morphology [26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…To explain this we have to adopt results of more sensitive, than ours experimental and simulations methods. Medlin et al 29,30 investigated the structure of the (0001) basal twin boundary in Bi 2 Te 3 with the use of high resolution electron diffraction (HAADF-STEM) supported by ab initio calculations. The interfacial atomic structure measurements showed that it is possible for the twin interface to be located at one of three distinct locations: at the Te(2) layer, the Bi layer, or the Te(1) layer.…”
Section: Discussionmentioning
confidence: 99%
“…In HAADF STEM mode, the image contrast is correlated with atomic mass, i.e., the atomic number Zdependence of the contrast is ~Z 2 , with application to the smallest U-bearing nanoparticles in environmental studies (e.g., Utsunomiya and Ewing 2003). Recent HAADF STEM studies of Pb-Bi sulfosalts, REE-fluorocarbonates, and Pb-Bi-or Bi-chalcogenides show how we can directly visualize structural blocks defining the homology of a mineral series and layer types in mixed-layer compounds (Medlin et al 2010(Medlin et al , 2013(Medlin et al , 2014(Medlin et al , 2019Ciobanu et al 2016Ciobanu et al , 2017Li et al 2019;Cook et al 2019).…”
Section: Introductionmentioning
confidence: 99%